2004
DOI: 10.1007/s11046-004-1819-3
|View full text |Cite
|
Sign up to set email alerts
|

First large-scale isolation of Prototheca zopfii from milk produced by dairy herds in Italy

Abstract: A total of 1045 milk samples collected from infected and non infected quarters of 269 cows were investigated. This study showed that 4.7% of samples possessed cells of Prototheca spp. (10(6)cells/ml). The presence of other pathogenic microorganisms was also monitored. Prototheca spp. isolates were classified on the basis of current taxonomic guidelines and identified as P. zopfii. Susceptibility tests carried out in vitro by using 25 antibiotic compounds revealed that the strains of P. zopfii. were susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 15 publications
6
33
2
6
Order By: Relevance
“…The results presented by Milanov et al (17) were comparable; all algae isolated from milk were also unsusceptible to enrofloxacin, amoxicillin, tetracycline, penicillin, lincomycin, and novobiocin. The obtained findings revealed that the highest antimicotic activity was demonstrated by nystatin, ketoconazole, and amphotericin B, which is consistent with the results of other authors confirming a high effectiveness of nystatin and amphotericin B against algae isolated from milk of mastitis-affected cows (5,7,14,17). Moreover, the results reported by Malinowski et al (10) were similar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results presented by Milanov et al (17) were comparable; all algae isolated from milk were also unsusceptible to enrofloxacin, amoxicillin, tetracycline, penicillin, lincomycin, and novobiocin. The obtained findings revealed that the highest antimicotic activity was demonstrated by nystatin, ketoconazole, and amphotericin B, which is consistent with the results of other authors confirming a high effectiveness of nystatin and amphotericin B against algae isolated from milk of mastitis-affected cows (5,7,14,17). Moreover, the results reported by Malinowski et al (10) were similar.…”
Section: Discussionsupporting
confidence: 90%
“…does not respond to the routine therapy of mastitis (9,15,16,21). The studies concerning in vitro and in vivo susceptibility of algae indicate their high resistance to antibacterial and antifungal antibiotics (4)(5)(6)11).…”
Section: Introductionmentioning
confidence: 99%
“…Prototheca mastitis is rapidly becoming a problem worldwide (BUZZINI et al, 2004;SCACCABAROZZI et al, 2008;RICCHI et al, 2010) and in the Republic of Serbia it was first diagnosed and described by MILANOV et al (2006) but without molecular characterization of Prototheca strains. Genotype-specific PCR assays, based on the 18S rDNA gene sequences, have recently been developed to differentiate three genotypes of Prototheca zopfii, of which Prototheca zopfii genotype 3 was reclassified in a new species Prototheca blaschkeae (ROESLER et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Algae from the genus Prototheca are the only plant-like microorganisms which can cause inflammation and alterations in the mammary gland (JAGIELSKI et al, 2011). Prototheca mastitis is rapidly becoming a problem worldwide (BUZZINI et al, 2004;SCACCABAROZZI et al, 2008;RICCHI et al, 2010) and in the Republic of Serbia it was diagnosed and described first by MILANOV et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most prevalent form of protothecosis in animals is bovine mastitis, which is characterized by acute to chronic pyogranulomatous inflammation of the mammary gland (Jánosi et al 2001). Bovine mastitis caused by P. zopfii has been extensively recognized as a considerable problem to the dairy industry worldwide (Castagna de Vargas et al 1998, Jensen et al 1998, Malinowski et al 2002, Buzzini et al 2004). The vast majority of the economic losses from protothecal mastitis are due to milk yield depression and premature culling of dairy cows, which, given the unresponsiveness of the algae to conventional therapy (Marques et al 2006, Lopes et al 2008, remains the only effective means of eliminating the disease.…”
Section: Introductionmentioning
confidence: 99%